Social Learning Theory and the Development of Aggression - Khadka, Chetan (Medha: A Multidisciplinary Journal, 2024)
This article explores the development of aggression through Social Learning Theory (SLT), emphasizing how aggression is acquired and reinforced within social environments. Developed by Albert Bandura, SLT highlights the role of observational learning, imitation, and reinforcement in shaping behavior. Notable studies, such as Bandura’s Bobo Doll experiment, illustrate how individuals, especially children, replicate aggressive behaviors when they observe others performing these actions, particularly when these behaviors are rewarded or accepted by society. The article delves into the impact of family dynamics, peer influences, and media exposure on aggression, emphasizing the role of both direct and vicarious reinforcement in sustaining aggressive behaviors. The findings suggest that interventions designed to reduce aggression should focus on altering the social environment by encouraging positive role models and controlling exposure to violent media. The article calls for more cross-cultural research to understand how social learning processes differ across various cultural contexts. Ultimately, it underscores the importance of social and environmental factors in the development of aggression. Practical recommendations are provided for parents, educators, and policymakers to foster environments that discourage aggression and encourage positive behavior. The article concludes by proposing directions for future research, particularly in exploring the long-term effects of observational learning and the interaction between social and biological influences on aggression.